Silicone Breast Implant/Tissue Expander Applications and Complication Management: Retrospective Patient Analysis of 172 Patients - Dinçer Altınel; Merdan Serin; Gaye Toplu (İstanbul Medical Journal, 2022)

(untitled)
Introduction:This study aimed to investigate the complications and their management following breast implant surgeries for patients undergoing breast augmentation, augmentation mastopexy and breast reconstruction.Methods:One hundred and seventy-two patients were included in this study. The implants were used to increase the breast volume, treat ptosis and for breast reconstruction in patients who had breast tissue removed completely or partially.Results:Overall complication rate was 76%. The complication rate in the breast augmentation group (n=60) was 76%. The complication rate in two session mastopexy augmentation groups (n=9) was 55%. The complication rate in the single session mastopexy augmentation group (n=27) was 66%. The complication rate in the breast reconstruction group (n=71) was 84.5%.Conclusion:Despite high complication rates, successful results can be obtained using correct patient selection, correct planning, correct implant selection, correct surgical technique and appropriate management of complications during the postoperative follow-up. The compliance of the patients to recommendations given by the surgeon during the follow-up and treatment process also is central to increasing the success rates.